Oxidative Stress as a Potential Mechanism Underlying Membrane Hyperexcitability in Neurodegenerative Diseases - Ricardo Pardillo-Díaz; Patricia Pérez-García; Carmen Castro; Pedro Nunez-Abades; Livia Carrascal (MDPI AG, 2022)
Neurodegenerative diseases are characterized by gradually progressive, selective loss of anatomically or physiologically related neuronal systems that produce brain damage from which there is no recovery. Despite the differences in clinical manifestations and neuronal vulnerability, the pathological processes appear to be similar, suggesting common neurodegenerative pathways. It is well known that oxidative stress and the production of reactive oxygen radicals plays a key role in neuronal cell damage. It has been proposed that this stress, among other mechanisms, could contribute to neuronal degeneration and might be one of the factors triggering the development of these pathologies. Another common feature in most neurodegenerative diseases is neuron hyperexcitability, an aberrant electrical activity. This review, focusing mainly on primary motor cortex pyramidal neurons, critically evaluates the idea that oxidative stress and inflammation may be involved in neurodegeneration via their capacity to increase membrane excitability.